Policy Model for Muslim State Inflation Control - Hamdan Firmansyah (UIN Sunan Gunung Djati Bandung, 2021)
Inflation is a problem which is not simple and is classified as an economic disease. Inflation is one important indicator in analyzing a country's economy, especially with regard to its broad impact on macroeconomic variables: economic growth, external balance, competitiveness, and even income distribution. Inflation is characterized by high and continuous increases in prices not only causing some adverse effects on economic activity, but also on the prosperity of individuals and society. An increase in the price of one or two items alone cannot be called inflation, unless the increase extends to an increase in the majority of other goods.